Sediment echosounder data (EdgeTech 3100 entire dataset) of Quarantine Bay, United States of America - Alexander Kolker; Dallon Weathers; Swann Christy; Renfro Alisha (PANGAEA, 2025)
This dataset contains sub-bottom seismic profiles collected in Quarantine Bay, located in southeastern Louisiana, USA, on the east side of the lower Mississippi River. Surveys were conducted on 23 September 2022, 25 September 2022, and 2 November 2022 to investigate the shallow subsurface stratigraphy of Quarantine Bay. These data were collected to support interpretations of delta development within the bay and to assess its relationship to Neptune Pass—the largest new distributary of the Mississippi River. The profiles also contributed to the calculation of sediment deposition as part of a broader sediment budget comparing erosion in Neptune Pass to deposition in Quarantine Bay. Data acquisition was performed using an Edgetech 3100-P CHIRP sub-bottom profiling system paired with an SB-216 towfish. Acoustic signals were transmitted in the 2–16 kHz frequency range, with typical penetration depths of approximately 1–5 meters below the seafloor. The study area extends from 29.432624°N to 29.375139°N latitude and from -89.522453°W to -89.458961°W longitude.